Phytochemical investigation of Suaeda baccata (chenopodiaceae) - Al-Mohammadi S. Suhad; Al-Khateeb Ekbal; Al-shamma Ali (College of Pharmacy / Mustansiriyah University, 2005)
This work covers some phytochemical studies of a wild plant, Suaeda baccata Forsk of the family Chenopodiaceae, which covers almost all the cities of Iraq. Literature survey revealed a number of publications concerning different species of Suaeda, but none at all concerned Suaeda baccata, therefore, a research on this plant will be of important value. Several reports indicated the presence of alkaloids in some Suaeda species, thus our investigation procedures emphasized the identification and isolation of the alkaloids that might be present in this plant. Preliminary investigation on the plant extract showed the presence of the alkaloids that were tested by both Mayer's reagent and Dragendorff's spraying reagent, and authenticated with standard compounds by TLC using several solvent systems that proved the presence of two alkaloids, trigonelline and choline. Trigonelline crystals were subjected to tests of purity as HPLC, melting point and mixed melting point, which matches with the standard trigonelline. Extract containing choline alkaloid was identified only by TLC using different solvent systems. Studies concerning its crystallization and identification by HPLC and melting point were left for further studies since choline is highly hygroscopic and oxidizable compound.